EFEKTIVITAS KONSELING KELOMPOK TERHADAP PENURUNAN PERILAKU AGRESIF PESERTA DIDIK KELAS X DI SMA TERAWAS - Herwantoro; Putri Rahmadani; Heri Rusmandi; Ifnaldi; Edi Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effectiveness of group counseling in reducing aggressive behavior among tenth-grade students at SMA Negeri Terawas. This research used a quantitative approach with an experimental method and a One Group Pretest-Posttest Design. The research subjects consisted of 10 tenth-grade students identified as having high levels of aggressive behavior through an initial questionnaire. Data collection techniques included aggressive behavior questionnaires, observation, and documentation. Data analysis used descriptive statistics and the Paired Sample t-Test. The results showed a decrease in students' aggressive behavior after receiving group counseling services. The mean pretest score of 82.5 decreased to 58.2 in the posttest. The results of the Paired Sample t-Test showed a significance value of 0.000 < 0.05, indicating that H0 was rejected and Ha accepted. Thus, group counseling was effective in reducing aggressive behavior among tenth-grade students at SMA Negeri Terawas.